Research on the Contemporary Significance of Creating the Sense of Community for the Chinese Nation: A Case Study of Red Education Cultural Relics in Guangdong - Wang, Xiaoxuan (Journal of Educational Theory and Practice, 2026)
At present, China is undergoing a period of profound transformation unseen in a century. Taking cultural relics related to revolutionary education as a focal point to promote the creative transformation and innovative development of China’s outstanding culture represents an effective pathway for the inheritance and development of Chinese culture, as well as for upholding a shared national spirit. This study takes educational cultural relics in Guangdong as its subject matter, integrating multidisciplinary perspectives from ethnology, cultural heritage studies, and pedagogy to construct a theoretical model of “cultural relics–cultural identity–sense of community” and to reveal its underlying operational logic and mechanisms of transformation. Concurrently, the study explores the logical connection between revolutionary educational cultural relics and the consolidation of a sense of community for the Chinese nation. It analyses how the creative transformation and innovative development of these cultural relics can help build outstanding cultures across all ethnic groups, thereby fostering a sense of community within the Chinese nation. It summarizes Chinese wisdom and solutions in this regard. This study posits that revolutionary educational cultural relics contribute to the formation of a shared understanding of the origins of Chinese education and represent a practical pathway to creating a shared historical memory. They are conducive to strengthening cultural identity with the great motherland, the Chinese nation, the Communist Party of China, and the path of socialism with Chinese characteristics.